Part of the people or apart from the people? - clinton peter verdonschot (Aesthetic Investigations)
Barbie (2023) is both a feminist and a metaphysical film. It is a story of ideas regarding girls and their fantasies and the relation of the two vis-à-vis each other. This critical note draws attention to a way in which the film's metaphysics gets in the way of its feminism. I will argue that the film's conception of Barbie Land and the Real World, as discrete planes of existence, is itself a symptom of the alienated state of existence that Barbie aims to overcome. Consequently, Barbie's escape from this alienated state is doomed to fail from the start.